Selective peroxynitrite-mediated protein nitration catalyzed by glyoxalase domain containing protein 4 - Sarah Wright; Vu C. Dang; Sami Hussain; Prasanna Kandel; Robert P. Brendza; Sahar Mazhar; Marie Whitmore; Selim Boudoukha; Jaskamaljot Kaur Banwait; Robert Van Der Linden; Edward Vertudes; Kate Markham; et al. (Proceedings of the National Academy of Sciences, 2026)
Tyrosine nitration alters the structure, function, and cellular localization of proteins and is implicated in the pathology of multiple diseases [G. Ferrer-Sueta et al. , Chem. Rev. 118 , 1338–1408 (2018), H. Ischiropoulos, Arch. Biochem. Biophys. 356 , 1–11 (1998), I. Griswold-Prenner et al. , J. Biol. Chem. 299 , 105038–10554 (2023)]. Although protein nitration is assumed to proceed via nonspecific chemical mechanisms, it is highly selective, suggesting the possibility of enzymatic catalysis. Here, we showed that glyoxalase domain-containing protein 4 (GLOD4), a previously uncharacterized protein, is an enzyme that catalyzes selective protein nitration. A primary in vivo target for GLOD4-mediated nitration is alpha-synuclein (α-syn), which is central to the pathogenesis of Parkinson’s disease (PD) and related disorders. We document tyrosine nitration of α-syn by GLOD4 in vitro, in cells, and in a murine model of synuclein pathology. The data identified a function of GLOD4 and other structurally related proteins that catalyze the peroxynitrite-mediated selective protein tyrosine nitration. This enzymatic catalysis of nitration may unearth pathophysiological mechanisms and potential interventions in diseases such as PD, cancer, and autoimmunity.